Penerapan meditasi dan afirmasi positif pada Ny. Y G4P2A1 gravida 37 minggu di Kabupaten Aceh Barat - Mutia, Cut; Zahara, Evi; Yushida, Yushida; Julianti, Rina (Femina: Jurnal Ilmiah Kebidanan, 2025)
Background: During pregnancy, various physiological and psychological changes occur. These changes occur due to changes in estrogen and progesterone hormone levels during pregnancy. One of the physiological changes is lower abdominal pain. Lower abdominal pain generally occurs when approaching the time of delivery. This is usually a signal that most of the lower part of the fetus is already completely in the pelvic cavity. The benefits of meditation can also be a psychological therapy without using chemical drugs that can interfere with pregnancy. The use of drugs in pregnant women requires special vigilance, some drugs can pose a risk to maternal health, and can have a direct effect on the fetus. Objective: to determine the effects of meditation and positive affirmations on Mrs. Y in overcoming pain in West Aceh Regency. Method: This care design is in the form of a case study with a qualitative approach. The subject of this case study is Mrs. Y, 30 years old G4P2A1, at 37 weeks of pregnancy with lower abdominal pain in West Aceh Regency. The study was conducted on February 8-15, 2025. Results: the results of the application of meditation and positive affirmations on Mrs. Y can reduce lower abdominal pain. Conclusion: the application of meditation and positive affirmation methods can reduce pain in pregnancy.